Proposal of a Measurement Scale and Test of the Impacts on Purchase and Revisit Intention - Ayari, Salma; Ben Yahia, Imène (Journal of Telecommunications and the Digital Economy, 2023)
Online immersion is considered as a determining factor of web surfers’ reactions. Its importance may be greater in a 3D-enriched environment. However, little research has explored it in marketing and less has investigated its impact on consumer behaviour in an enriched commercial website. In addition, when it comes to its operationalization, many weaknesses are noticed in the existing literature. Accordingly, the objective of this study is two-fold: in order to test the impact of immersion on purchase and revisit intentions to a 3D-enriched commercial website, a scale measurement of immersion tailored to this specific context is proposed. Following Churchill’s framework and the recommendations of Rossiter, a number of methodological instruments, including two focus groups (the first with 4 experts; the second with 18 consumers) and three surveys (first: 140 students; second: 350 Internet users; third: 200 Internet users), are used. The confirmatory factor analysis resulted in an 8-item scale which seems to exhibit evidence of reliability and validity. The predictive validity was confirmed since the impacts of immersion on the intentions to buy and revisit the website are significant. The proposed scale measure may help academics conduct better and more reliable studies on consumer behaviour online.